2023
DOI: 10.3390/plants12040710
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Biological Functions of 9-cis-Epoxycarotenoid Dioxygenase Genes Involved in Seed Dormancy in Paeonia lactiflora

Abstract: Abscisic acid (ABA) is a major phytohormone affecting seed dormancy and germination in plants. ABA is synthesized mainly through the C40 carotenoid pathway. In the ABA biosynthesis pathway, 9-cis-epoxycarotenoid dioxygenase (NCED) is a key rate-limiting enzyme that regulates the accumulation and content of ABA. However, the role of the NCED gene in perennial plants with complex seed dormancy remains largely unknown. Here, we cloned two differentially expressed paralogs of herbaceous peony NCED genes, named PlN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Fei et al identified and cloned two genes from the NCED family in Paeonia lactiflora, which are related to ABA synthesis in the herbaceous peony, named PlNCED1 and PlNCED2. Further studies confirmed the function of the PlNCED gene in inducing seed dormancy and hindering seed germination [4]. In iris plants, Wang et al confirmed the function of the AP2/ERF superfamily member IlAP2, which interacts with IlMT2a, in enhancing Cd tolerance [5].…”
Section: Gene Function Researchmentioning
confidence: 90%
“…Fei et al identified and cloned two genes from the NCED family in Paeonia lactiflora, which are related to ABA synthesis in the herbaceous peony, named PlNCED1 and PlNCED2. Further studies confirmed the function of the PlNCED gene in inducing seed dormancy and hindering seed germination [4]. In iris plants, Wang et al confirmed the function of the AP2/ERF superfamily member IlAP2, which interacts with IlMT2a, in enhancing Cd tolerance [5].…”
Section: Gene Function Researchmentioning
confidence: 90%
“…The identification of the NCED gene marked a significant milestone in advancing our comprehension of ABA production and its role in plant growth and development. The NCED gene was initially cloned in the maize ABA-deletion mutant Vp14, leading to a better understanding of NCED's involvement in ABA synthesis (Fei et al, 2023). Further research in Arabidopsis revealed nine CCOs genes, five of which (AtNCED2, AtNCED3, AtNCED5, AtNCED6, and AtNCED9) are involved in ABA synthesis (Hu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of NCED promotes ABA accumulation and delays seed germination (Wang et al, 2011), which is consistent with the results of this study. Previous reports indicate that ABA controls root elongation by regulating auxin biosynthesis, distribution and transport (Chen et al, 2016;Fei et al, 2023). High concentrations of exogenous auxin inhibit seed germination in A. thaliana, while low concentrations promote seed germination (He et al, 2012).…”
mentioning
confidence: 99%